Changing Workplace Culture – What Would It Take to Speak Up? - Millis, Sandra (Operating Room Nurses Association of Canada Journal, 2019)
Bullying in the healthcare environment historically has been tolerated, and in many cases expected. The Health and Safety at Work Act (2015) has provided the necessary legislation to stimulate a move toward addressing the bullying culture within New Zealand hospitals. This article takes a reflective look at how speaking up about bullying, although difficult, is important in order to change work place culture.